The Guidelines of Researches of Senility, Aging and Functioning of Old People: a Byopsychosocial Approach - Bagdonas, Albinas; Kairys, Antanas; Zamalijeva, Olga (Socialinė teorija, empirija, politika ir praktika, 2017)
The application of the WHO biopsychosocial approach to the researches of senility, aging and life problems of old people (ICF) is reviewed. After a brief presentation of aging statistics in Lithuania, the semantic field of using terms in the area of life periodization is discussed and the names for each period and sub-period are proposed. The composition of the ICF model (body structures and functions, activities, participation and contextual factors) is presented, together with the usage of components of the ICF model in researches regarding senility. New conceptions of a “functioning reserve” and the “integral aspects of functioning” are proposed and incorporated in the ICF model. A review of researches of psychological well-being of old people – one of the integral aspects of functioning of old people in Lithuania – is presented. There is a very good coherence of views between the authors of this paper on the topic of senility and the misconceptions of aging and health, which were recently presented by WHO.